STRATEGI PENGEMBANGAN SUKUK KORPORASI DI INDONESIA: METODE ANALYTICAL HIERARCHY PROCESS (STRATEGY OF COORPORATION SUKUK DEVELOPMENT IN INDONESIA: ANALYTICAL HIERARCHY PROCESS METHOD) - Lokot Zein Nasution (Inovasi, 2017)
On a global scale, the growth rate of corporate sukuk goes great. However, the trend of development at the domestic level is running very slowly. Therefore, this research succeeded in finding the root of the problem and the development strategy of corporate sukuk in Indonesia. Based on the results of sukuk not yet drawn much by market participants; (i) due to problems from supply side; and (ii) due to problems from side requests. The first root, namely: (i) the cost of issuance of sukuk is still expensive; (ii) limited sukuk liquidity in the secondary market; (iii) characteristics of complex sukuk structures; (iv) the complexity of the sukuk document; and (v) low variation of sukuk contract. The root of the second phase event consists of five factors, namely: (i) investor's understanding of the sukuk character; (ii) the value of the issuer of the sukuk character; (iii) unpublished investor base; (iv) accounting standards are still unclear; And (v) low variation of contract. Meanwhile, due to: (i) the unavailability of supporting profession in the sukuk market; (Ii) the lack of socialization and education on information about the association; (iii) unavailability of supporting industries; and (iv) the limited quality of human resources of the sukuk principals. Based on the Analytical Hierarchy Process (AHP) analysis, namely: (i) establishing regulation concerning the supporting profession in the sukuk market; (ii) to make regulation of socialization and education concerning sukuk instruments; and (iii) provide supporting industries for the sukuk market. These results can serve as a reference in strategies for strengthening appropriate strategies to foster sukuk development over the long term Keywords: sukuk characteristic, supply problems, demands problems